2010
DOI: 10.1177/0164027510384711
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Religious Similarity in the Quality of Mother-child Relations in Later Life: Differences Within Families and Between Races

Abstract: Despite evidence of the importance of value similarity in predicting parent-adult child relations, little attention has been given to the unique role of religious similarity. Using 1,407 dyads nested within 390 families, we examine whether religious similarity predicts the quality of mother-child relations in later life, and whether the strength of this association differs by race. Consistent with our hypotheses, religious similarity was found to be an important factor in predicting both closeness and conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…Gilligan, 1982;Rossi & Rossi, 1990). Consistent with this argument, the literature has shown that similarity is a strong predictor of mothers' relationships with their adult children (Rossi & Rossi, 1990;Sechrist, Suitor, Vargas, & Pillemer, 2011;Suitor, Gilligan, & Pillemer, 2013a). Furthermore, panel studies have revealed that perceived value similarity between mothers and adult children at one point predicts greater closeness at later points (Suitor et al, 2013a).…”
Section: Value Similaritymentioning
confidence: 86%
“…Gilligan, 1982;Rossi & Rossi, 1990). Consistent with this argument, the literature has shown that similarity is a strong predictor of mothers' relationships with their adult children (Rossi & Rossi, 1990;Sechrist, Suitor, Vargas, & Pillemer, 2011;Suitor, Gilligan, & Pillemer, 2013a). Furthermore, panel studies have revealed that perceived value similarity between mothers and adult children at one point predicts greater closeness at later points (Suitor et al, 2013a).…”
Section: Value Similaritymentioning
confidence: 86%
“…Limitations should be considered. Analyses rely on the perspectives of adult children; a more comprehensive study would include accounts from both parents and adult children as adult children's descriptions may be reflective of, or perhaps diverge from, the perceptions of parents Gilligan, Suitor, Kim, & Pillemer, 2013;Reczek, 2014;Sechrist et al, 2011). Multiple accounts may be particularly important when attempting to understand the consequences of these intergenerational exchanges on both generations.…”
Section: Discussionmentioning
confidence: 99%
“…The analytical sample was restricted to individuals aged 40 and older to situate the analysis in theory and research on midlife to later life adults (Birditt et al, 2010;Moen & Wethington, 1999). Both members of a couple were interviewed separately in order to obtain independent accounts (Sechrist, Suitor, Vargas, & Pillemer, 2011). In four sample couples, one individual was younger than 40 years and one individual older than 40 years; the individual older than 40 years remained in the analytical sample, whereas the individual younger than 40 years was removed in order to adhere to the age restriction of the study; partners younger than 40 years who were not analyzed are listed with a superscript letter "a" in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Behavior is typically represented as attendance at religious services, belonging to an affiliation, and belief as subscribing to religious doctrine and sometimes religious salience (Hwang et al, 2018). The degree of emotional intimacy between parents and adult children is positively predicted by cross-generational similarities in religious values (Sechrist, Suitor, Vargas, & Pillemer, 2011), religious attendance (Pearce & Axinn, 1998), and religious affiliation (Hwang et al, 2018). Other aspects of parent-child relationships are also sensitive to religious concordance between generations.…”
Section: Religion and Intergenerational Relationsmentioning
confidence: 99%